13-5z=1

Simple and best practice solution for 13-5z=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-5z=1 equation:


Simplifying
13 + -5z = 1

Solving
13 + -5z = 1

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -5z = 1 + -13

Combine like terms: 13 + -13 = 0
0 + -5z = 1 + -13
-5z = 1 + -13

Combine like terms: 1 + -13 = -12
-5z = -12

Divide each side by '-5'.
z = 2.4

Simplifying
z = 2.4

See similar equations:

| 3/x^2-3x | | K-(-5)=20 | | 3(y-1)+6=9 | | 13v-4v+2v=-22 | | ((x^2-2x-24)/(4x^3-5x^2))*((x^3-x^2)/(2x-12)) | | -4x+2=-2(3y+3) | | -2(m-3)=-6m+8 | | -7=-5-K | | x-1/2-7=x-1/3 | | D(x)=-6/x^2-9 | | 100+-53= | | 25/187.50 | | -2m-6=-6m+8 | | 6(x-2)-x=4(x+4)+7 | | -5y=-20+-25 | | 15=10p-5-3p | | -6/x^2-9 | | -2.6(x-8)+4.2=11 | | 187.5/25 | | x^2=x^2-3x | | -5y=-20+-20 | | 3a+3-11a=3a+36 | | logb81=2/3 | | u-7+2(2u+1)=-7(u+2) | | -16t^2+10t+50=0 | | 2x-10=-59+9z | | s-(5-3x)=7x+4 | | 5y+1+y=3y+19 | | -1(2-2n)=0 | | 5y+1+y=3y | | 2(6x+7)+9=12x+23 | | (2x+9)+6=2 |

Equations solver categories